Management of epidemic COVID-19 crisis in Gorgan, north of Iran (February 2020 to May 2020) - Alireza Norouzi; Afshin Sardarzade Majd; Behzad Vatankhah; Nafiseh Abdolahi; Samaneh Tavassoli; Abdolreza Fazel; Asieh Khalili; Somayeh Pasandi; Saba Besharat (مجله دانشگاه علوم پزشکی گرگان, 2020)
In December 2019, the new acute respiratory disease spread in China presented with fever and dry cough known to be resulted from the new Corona Virus as the COVID-19. In Iran, the first case was reported on 20th of February 2020. Our management team in Golestan University of Medical Sciences held an immediate meeting to decide how to manage the cases suspected to the COVID-19.The two main hospitals had been selected as the Corona center in the Golestan province, northern Iran. Admitting patients other than COVID-19 has been stopped in these hospitals, and all patients had been transferred to the other hospital in Gorgan city and those in the recovery state had been transferred to a hotel prepared for this purpose. The capacity of Sayyad-e-Shirazi hospital was 300 bed for admission and 25 ICU beds that had been increased to 44 ICU beds (30 percent increases) to be prepared for COVID-19 admission. Clinical groups and specialists had been organized with special duty for each part. After 3 months of COVID-19 crisis, Sayyad-e-Shirazi hospital with 300 beds is in a good shape and admission of severe cases has been decreased.